2017
DOI: 10.1074/jbc.m117.784256
|View full text |Cite
|
Sign up to set email alerts
|

Nischarin inhibition alters energy metabolism by activating AMP-activated protein kinase

Abstract: Nischarin (Nisch) is a key protein functioning as a molecular scaffold and thereby hosting interactions with several protein partners. To explore the physiological importance of Nisch, here we generated Nisch loss-of-function mutant mice and analyzed their metabolic phenotype. Nisch-mutant embryos exhibited delayed development, characterized by small size and attenuated weight gain. We uncovered the reason for this phenotype by showing that Nisch binds to and inhibits the activity of AMP-activated protein kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 56 publications
2
26
3
Order By: Relevance
“…41 Previously, we have shown that Nischarin interacts with AMPK and affects AMPK functions in mouse embryonic fibroblasts (MEFs), where we showed that deletion of Nischarin in MEFs enhances AMPK phosphorylation. 18 These data seemingly are contradictory with the current data. Although we do not know the exact reason for these differences, we suspect that acquiring cancer phenotype due to the presence of PyMT gene somehow underlies these changes.…”
Section: Discussioncontrasting
confidence: 71%
See 4 more Smart Citations
“…41 Previously, we have shown that Nischarin interacts with AMPK and affects AMPK functions in mouse embryonic fibroblasts (MEFs), where we showed that deletion of Nischarin in MEFs enhances AMPK phosphorylation. 18 These data seemingly are contradictory with the current data. Although we do not know the exact reason for these differences, we suspect that acquiring cancer phenotype due to the presence of PyMT gene somehow underlies these changes.…”
Section: Discussioncontrasting
confidence: 71%
“…44 Furthermore, IQGAP1 has been shown to promote carcinogenesis 42 and thus suggested to be a rheostat at the interface of cancer and diabetes. Our published data indicate that Nischarin mutation enhances AMPK activation in mouse embryonic fibroblasts to regulate energy homeostasis, 18 while the current study shows the activation is low in Nischarin mutant PyMT tumors to regulate tumor growth. Hence, Nischarin may likely function as a rheostat for balancing AMPK activation in energy homeostasis of embryonic fibroblasts and tumorigenesis of cancer cells.…”
Section: Discussioncontrasting
confidence: 47%
See 3 more Smart Citations